2017
DOI: 10.1016/j.celrep.2017.11.060
|View full text |Cite
|
Sign up to set email alerts
|

The Germline Linker Histone dBigH1 and the Translational Regulator Bam Form a Repressor Loop Essential for Male Germ Stem Cell Differentiation

Abstract: Drosophila spermatogenesis constitutes a paradigmatic system to study maintenance, proliferation, and differentiation of adult stem cell lineages. Each Drosophila testis contains 6-12 germ stem cells (GSCs) that divide asymmetrically to produce gonialblast cells that undergo four transit-amplifying (TA) spermatogonial divisions before entering spermatocyte differentiation. Mechanisms governing these crucial transitions are not fully understood. Here, we report the essential role of the germline linker histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 57 publications
(89 reference statements)
5
26
0
Order By: Relevance
“…homozygous embryos experience changes in chromatin structure, premature activation of zygotic transcription, and ultimately death. Carbonell et al 2017 concluded that reducing BigH1 in testis results in a severe disruption of male establishment and no premature activation of typical zygotic genes ( Figure S4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…homozygous embryos experience changes in chromatin structure, premature activation of zygotic transcription, and ultimately death. Carbonell et al 2017 concluded that reducing BigH1 in testis results in a severe disruption of male establishment and no premature activation of typical zygotic genes ( Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both embryonic and male germline defects were reported for mutant animals (Pérez-Montero et al 2013;Carbonell et al 2017). However, the facts that BigH1 is loaded maternally, and that BigH1 is replaced by H1 before the activation of the zygotic genome, are conceptually inconsistent with the recessive zygotic lethality described for the bigH1 mutant in the 2013 study.…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, H1 complexity is low since it encodes for a single ubiquitously expressed somatic dH1 variant and a single germline specific dBigH1 variant (reviewed in Bayona-Feliu et al, 2016). dBigH1 is expressed in both the female and male germline, and it is present in the early embryo until zygotic genome activation (ZGA) at cellularization (Carbonell et al, 2017;Pérez-Montero et al, 2013). At this stage, dBigH1 is replaced by somatic dH1 in somatic cells, whereas it is retained in the primordial germ cells (PGC) (Pérez-Montero et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila , an alternative linker histone BigH1 is present in the early embryo and in the male and female germline ( 12 , 30 ). To study the specific developmental role of BigH1, we generated transgenic animals that express chimera linker histones constructed by domain switches between somatic H1 and germline/early embryo-specific BigH1.…”
Section: Discussionmentioning
confidence: 99%